Kinerja Lingkungan, Kepemilikan Manajemen, Media Exposure dan Corporate Social Responsibility Disclosure - Arikarsita, Ni Wayan; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2020)
Corporate Social Responsibility Disclosure is a form of corporate responsibility and commitment in making a positive contribution to the environment, social and economy that is integrated in the company's activities. This study aims to obtain empirical evidence regarding the effect of environmental performance, management ownership, and media exposure on corporate social responsibility disclosure. This research was conducted at manufacturing companies listed on the IDX and registered as participants in the 2016-2018 PROPER period. The sampling method used is purposive sampling. Data collection methods used in this study are non-participant observation methods and documentation. This study uses data analysis techniques in the form of multiple linear regression analysis.The analysis shows that environmental performance, management ownership, and media exposure partially have a positive effect on corporate social responsibility disclosure. Keywords: Environmental Performance; Management Ownership; Media Exposure; Corporate Social Responsibility Disclosure.